Positioning using UWB-IR and IMU - Lang, Hao (Nanyang Technological University, 2021)
This dissertation is concentrated on how to reduce the number of UWB (Ultra wide-band Impulse Radio) anchor nodes while maintaining certain level of positioning accuracy by integration with IMU (Inertia Mesurement Unit). Meanwhile, the accumulated errors of IMU positioning introduced by integration can be calibrated using UWB measurements. Important properties of UWB-IR and IMU sensors are introduced. The positioning method and drifts calibration of IMU are discussed as well as the ranging method of UWB-IR standalone. Loose coupling and tight coupling are chosen to integrate the UWB-IR position data with IMU sensors data. Compared to the single positioning method, both of the fusion approaches can offer better accuracy. The tight coupling performs better on the NLOS conditions. The experiments and result analyses were mainly implemented on the Raspberry Pi with Python.